Effect of High-Temperature Annealing on Ion-Implanted Silicon Solar Cells - Hyunpil Boo; Jong-Han Lee; Min Gu Kang; KyungDong Lee; Seongtak Kim; Hae Chul Hwang; Wook Jung Hwang; Hee Oh Kang; Sungeun Park; Sung Ju Tark; Donghwan Kim (International Journal of Photoenergy)
P-type and n-type wafers were implanted with phosphorus and boron, respectively, for emitter formation and were annealed subsequently at 950∼1050∘C for 30∼90 min for activation. Boron emitters were activated at 1000∘C or higher, while phosphorus emitters were activated at 950∘C. QSSPC measurements show that the implied Voc of boron emitters increases about 15 mV and the J01 decreases by deep junction annealing even after the activation due to the reduced recombination in the emitter. However, for phosphorus emitters the implied Voc decreases from 622 mV to 560 mV and the J01 increases with deep junction annealing. This is due to the abrupt decrease in the bulk lifetime of the p-type wafer itself from 178 μs to 14 μs. PC1D simulation based on these results shows that, for p-type implanted solar cells, increasing the annealing temperature and time abruptly decreases the efficiency (Δηabs=−1.3%), while, for n-type implanted solar cells, deep junction annealing increases the efficiency and Voc, especially (Δηabs=+0.4%) for backside emitter solar cells.